The Development of Voice Over as Drama Media to Teach Speaking Skill in English 8th Grade of Junior High School - Liastaria, Julia Rahayu; Widiarini; Saifudin, Ahmad (PROJECT (Professional Journal of English Education), 2025)
This research focuses on developing engaging learning media to teach speaking skills to eighth grade students at MTSN 1 Sanankulon. Traditional methods of English instruction frequently fail to engage students, hindering their active participation and limiting their progress. To overcome this problem, this study introduces Voice over as drama media as a language learning tool. The game helps to increase students' activeness and creativity, vocabulary acquisition, and confidence in speaking. An R&D approach, including a pilot test with 25 students, was used to assess the effectiveness of the game. The results showed that the Voice over as drama media significantly improved learning, with a questionnaire score of 86.1%, categorized as highly valid. The evaluation showed that this media is a highly effective teaching tool. This research shows that Voice over as drama media can improve students' speaking ability and create a more interesting learning environment. This approach is in line with modern educational trends that emphasize interactive, creative and student-centered learning. In conclusion, Taboo game is an effective solution to teach speaking skills and increase students' motivation.